Multi-omic stock of surface ocean microbiome built by monthly, weekly and daily sampling in Dapeng Bay, China - Yanwei Chen; Siruo Chen; Jianchang Tao; Minxu Li; Wenxiu Wang; Mei Chen; Xiaochen Fang; Lingchao Kong; Yidong Wang; Olivier Pereira; Chuanlun Zhang (Scientific Data)
Abstract The coastal ocean is the dynamic interface where terrestrial, atmospheric, and marine systems converge, acting as a hotspot for microbial activity, which underpins the intricate web of carbon and nitrogen cycling. Dapeng Bay, a typical semi-enclosed bay along the southern coastline of China, is strongly influenced by monsoon climates and human activities. Despite its ecological importance, long-term observations and investigations into the microbial community structure in this region are notably lacking. To address this gap, we conducted a two-year continuous sampling from May 2021 to June 2023 to explore shifts in nearshore surface microbial communities and assess the long-term effects of environmental stressors. This study presents comprehensive amplicon, metagenomic, and metatranscriptomic information. We identified 3,600 amplicon sequence variants and recovered 1,216 high-quality metagenome-assembled MAGs, representing 17 bacterial and 3 archaeal phyla. Additionally, 587 MAGs were correlated with transcriptional activity, comprising 539 bacterial and 48 archaeal populations. This dataset is anticipated to provide a multi-dimensional perspective, enhancing our understanding of the complexity, dynamics, and adaptability of microbial communities in coastal environments.